Cochrane Database of Systematic Reviews 2003
DOI: 10.1002/14651858.cd003669
|View full text |Cite
|
Sign up to set email alerts
|

Regional (spinal, epidural, caudal) versus general anaesthesia in preterm infants undergoing inguinal herniorrhaphy in early infancy

Abstract: There is no reliable evidence from the trials reviewed concerning the effect of spinal as compared to general anaesthesia on the incidence of post-operative apnoea, bradycardia, or oxygen desaturation in ex-preterm infants undergoing herniorrhaphy. The estimates of effect in this review are based on a total population of only 108 patients or fewer.A large well designed randomised controlled trial is needed to determine if spinal anaesthesia reduces post-operative apnoea in ex-preterm infants not pretreated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 11 publications
0
63
0
2
Order By: Relevance
“…Indeed, Craven et al published a Cochrane Collaboration analysis in which only 108 patients from 4 small randomized or quasi-randomized studies comparing spinal and general anesthesia were identified. 44 The authors concluded that there was no evidence that spinal anesthesia was associated with a reduction in postoperative apnea, bradycardia, or oxygen desaturation. Furthermore, the authors concluded that a large, randomized controlled trial was necessary to determine whether spinal anesthesia reduces postoperative cardiorespiratory complications; to date, no such study has been reported.…”
Section: Rationale and Timing For Elective Inguinal Hernia Repair In mentioning
confidence: 99%
“…Indeed, Craven et al published a Cochrane Collaboration analysis in which only 108 patients from 4 small randomized or quasi-randomized studies comparing spinal and general anesthesia were identified. 44 The authors concluded that there was no evidence that spinal anesthesia was associated with a reduction in postoperative apnea, bradycardia, or oxygen desaturation. Furthermore, the authors concluded that a large, randomized controlled trial was necessary to determine whether spinal anesthesia reduces postoperative cardiorespiratory complications; to date, no such study has been reported.…”
Section: Rationale and Timing For Elective Inguinal Hernia Repair In mentioning
confidence: 99%
“…Only 27 systematic reviews were read in full text, but 9 were excluded because they were not compatible with the inclusion criterion, and 8 were published in more than one journal or cited more than once in databases. This process left us with 10 systematic reviews for qualitative analysis [8][9][10][11][12][13][14][15][16][17] . Kappa statistics for screening systematic reviews was 0.82.…”
Section: Resultsmentioning
confidence: 99%
“…We avoided general anesthesia, due to this knowledge. However, Craven et al have claimed that there was no reliable evidence in the reviewed trials concerning the effect of spinal anesthesia on the incidence of postoperative apnea, bradycardia, or oxygen desaturation in ex-preterm preterm infants undergoing hernia repair, when compared to general anesthesia [7] this issue is controversial.…”
Section: Discussionmentioning
confidence: 99%